Cost Effective NSX Inventory State Management in Cross Cloud - (:unkn) unknown (My University, 2017)
With the extreme grown in technology, the amount of data that belong to an organization is many folded. It is practically impossible to persist entire data on premises. So many organizations are turning towards cloud. So the focus is on cross-cloud environment where NSX manager that manages both on premise and public cloud workflow is deployed on premises of an enterprise customer. In such a situation, data must be sent to the public cloud environment. But there are certain fault scenarios, which require whole data to be sent again and again to cloud. The aim is to reduce the amount of data being sent in such situations and find the current cost of maintaining inventory information.
M.Tech. (Computer Science and Application)
Keywords: Cross Cloud; NSX Inventory; Inventory State Management